An evolutionary approach to the extraction of object construction trees from 3D point clouds. (May 2016) - Fayolle, Pierre-Alain; Pasko, Alexander
Abstract: In order to extract a construction tree from a finite set of points sampled on the surface of an object, we present an evolutionary algorithm that evolves set-theoretic expressions made of primitives fitted to the input point-set and modeling operations. To keep relatively simple trees, we use a penalty term in the objective function optimized by the evolutionary algorithm. We show with experiments successes but also limitations of this approach. Highlights: An algorithm for extracting an object from a 3D point-cloud. An evolutionary approach for combining primitives, fitted to the input point-cloud, by modeling operations. A technique for limiting the size of the evolved model to allow its reusability.